Performance evaluation of brinjal genotypes in the mid-hill region of Gandaki Province, Nepal (Nepal Agriculture Research Journal, 2023)
Six genotypes of brinjal were evaluated at the Horticulture Research Station, Malepatan to identify the potential genotype for mid-hills of Gandaki province in the month of May 2020 and 2021. Experiments were conducted in a Randomized Complete Block Design (RCBD) with four replications. The genotypes were Jumli Local, Parwanipur Selection 1, Pusa Purple Long, Tanahun Collection, Takunchaur Collection, and Pokhara Lurkee. There were significant (p